Chemical interaction and enhanced interfacial ion transport in a ceramic nanofiber–polymer composite electrolyte for all-solid-state lithium metal batteries. Issue 15 (1st April 2020) - Yang, Hui; Bright, Joeseph; Chen, Banghao; Zheng, Peng; Gao, Xuefei; Liu, Botong; Kasani, Sujan; Zhang, Xiangwu; Wu, Nianqiang
Abstract : This article shows strong chemical interaction between a ceramic and polymer in a solid-state composite electrolyte and three Li-ion transport pathways. Abstract : This paper reports the synergy between ceramic nanofibers and a polymer, and the enhanced interfacial Li-ion transport along the nanofiber/polymer interface in a solid-state ceramic/polymer composite electrolyte, in which a three-dimensional (3D) electrospun aluminum-doped Li0.33 La0.557 TiO3 (LLTO) nanofiber network is embedded in a polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) matrix. Strong chemical interaction occurs between the nanofibers and the polymer matrix. Addition of the ceramic nanofibers into the polymer matrix results in the dehydrofluorination of the PVDF chains, deprotonation of the –CH2 moiety and amorphization of the polymer matrix. Solid-state nuclear magnetic resonance (NMR) spectra reveal that lithium ions transport via three pathways: (i) intra-polymer transport, (ii) intra-nanofiber transport, and (iii) interfacial polymer/nanofiber transport. In addition, lithium phosphate is coated on the LLTO nanofiber surface before the nanofibers are embedded into the polymer matrix. The presence of lithium phosphate at the LLTO/polymer interface further enhances the chemical interaction between the nanofibers and the polymer, which promotes the lithium ion transport along the polymer/nanofiber interface. This in turn improves the ionic conductivity and electrochemical cycling stability of the nanofiber/polymer composite. As a result, the flexible LLTO/Li3 PO4 /polymer composite electrolyte membrane exhibits an ionic conductivity of 5.1 × 10 −4 S cm −1 at room temperature and an electrochemical stability window of 5.0 V vs. Li/Li + . A symmetric Li|electrolyte|Li half-cell shows a low overpotential of 50 mV at a constant current density of 0.5 mA cm −2 for more than 800 h. In addition, a full cell is constructed by sandwiching the composite electrolyte between a lithium metal anode and a LiFePO4 -based cathode. Such an all-solid-state lithium metal battery exhibits excellent cycling performance and rate capability.